Contenido original: la apuesta estratégica de las plataformas de streaming. El caso Netflix en Latinoamérica (Monográficos) - Heredia Ruiz, Verónica (2022)
Original content has become the main differentiator of SVOD (Subscription Video on Demand) platforms. Netflix, Amazon Prime Video, Disney+, HBO Max, Apple Tv Plus have consolidated their expansion strategy on the promise of having original, exclusive and global productions, in order to satisfy the tastes and expectations of their subscribers. In this race for differentiation, Netflix today has established itself as the leader in streaming entertainment. Netflix arrives in Latin America in 2011. This article aims to explore the original content produced in Latin America, especially fiction series, between 2015 and 2021 in the Netflix catalog and seeks to answer the following questions: What is the strategic commitment to Netflix original content in Latin America? What characteristics do they have and what themes do these original content address? In which countries are these productions mainly carried out? It is concluded that local original content with a global vision and that generates cultural proximity are differentiating elements of the Netflix Originals catalog in Latin America. Countries such as Mexico, Brazil, Argentina and Colombia have been fundamental in the expansion and production of original content, thanks to Netflix’s strategic alliance with local production companies, to create content that responds to the tastes of the platform’s audiences and at the same time, generate identification with the Latin American public.